Cooperative content downloading scheme based on D2D multicast communications - Lianxin YANG; Dan WU; Feng YUAN; Chao YUE; Qinxue FU (Tongxin xuebao)
Aiming at the content downloading scenario in the network such as cellular network and vehicular network,a cooperative content downloading scheme based on device-to-device multicast communications was proposed to improve the content downloading performance.Such a scheme took advantage of the proximity feature of the content requesters and groups them into disjoint clusters.Firstly,the base station delivered the entire content to a cluster,and each content requester in a cluster downloaded a proportion of the entire content.Then,the content requesters took turns sharing their downloaded content with other content requesters in the same cluster.In this way,the additional resource consumption of content sharing in a cluster was shared by the content requesters in the cluster together.During this process,a pricing-based approach was proposed to motivate these content requesters to cooperate with each other.Such an approach only required the base station to maintain a content downloading price.Based on this,the joint issue of user clustering,link scheduling and power allocation was studied to minimize the total cost of content requesters.To obtain a superior solution with reductive complexity,a joint optimization algorithm was designed based on the coalition formation game.Numerical results show that compared with the traditional non-cooperative scheme,the total cost of content requesters was reduced by 37.15%.Under different numbers of content requesters and cellular users,the proposed scheme is both superior to other benchmark schemes.